Biomass Origin Waste as Activators of the Polyurethane Foaming Process - Patrycja Zakrzewska; Beata Zygmunt-Kowalska; Monika Kuźnia; Artur Szajding; Tadeusz Telejko; Małgorzata Wilk (Energies, 2023)
Rigid polyurethane foams (RPUFs) are characterized by their excellent viable properties; thus, these materials can be successfully used as thermal insulation materials. The main problem, the solution of which is partly indicated in this paper, is that the products for the synthesis of RPUFs are produced from petrochemicals. Due to this, the use of natural fillers in the form of waste biomass is introduced for the synthesis of RPUFs. The biodegradable biomass waste used in the RPUF production process plays multiple roles: it becomes an activator of the RPUF foaming process, improves selected properties of RPUF materials and reduces the production costs of insulating materials. The paper presents the results of the foaming process with the use of six different fillers: sunflower husk (SH), rice husk (RH), buckwheat husk (BH), sunflower husk ash (SHA), rice husk ash (RHA) and buckwheat husk ash (BHA). In all cases, composites of rigid polyurethane foam with 10 wt.% of filler were produced. New foams were compared with polyurethane materials without the addition of a modifier. Moreover, the paper presents the results of the fillers’ analysis used in the tests and the effects of the fillers’ addition as activators of the RPUF foaming process. Promising results were obtained for two of the fillers, BHA and SHA, as activators of the foaming process and confirmed by the volumetric results, where the named samples reached their maximum value in half the time compared to the remaining samples. In addition, the expansion rate for PU_10BHA was a maximum of approximately 11 cm3/s and PU_10SHA was a maximum of approximately 9 cm3/s, whereas the remaining samples showed this parameter at about 3 cm3/s. During the research, the scanning electron microscopy method and infrared camera technique were used.